Misunderstanding of Islam in Ayaan Hirsi Ali’s Speech Based on Islamic Perspective: A Semiotic Analysis - Diana Eka Sari; Aninda Aji Siwi (Journal of English Language Teaching and Linguistics, 2024)
Islam is often misunderstood as a bad religion in the West. This prejudice increased rapidly after the terror act that brought down the WTC towers in New York by radical Muslims on September 11, 2001. This prejudice developed to give birth to Islamophobia which is still spreading in the West, including in speeches. One of the speeches containing misunderstandings and prejudice against Islam is Ayaan Hirsi Ali's speech Liberal Democracies in An Era of Jihad and Mass Migration which considers Islam to be a bad and radical religion. This research aims to refute misunderstandings of Islam in Ayaan Hirsi Ali's speech Liberal Democracies in An Era of Jihad and Mass Migration so that bad thoughts about Islam can change and the phenomenon of Islamophobia can be reduced. This research is a qualitative descriptive method using the semiotic theory of Ferdinand de Saussure and also Islamic perspective to refute Ayaan's misunderstandings about Islam in the analysis. The results of this research show several of Ayaan's misunderstandings about Islam which are contrary to the Islamic perspective, such as whatever the Prophet Muhammad did during his lifetime must also be done by his people in the present, the Prophet Muhammad was a cruel person, all Madaniyah verses like a war manual because it only contains war, Muslim men indoctrinated to be selfish, Muslim women restrained, Muslim men are selfish, Islamic law is bad for everyone, and Islamic law is a cult of death because it only contains massacres and sacrifice of life.